Crystal structure of steroid reductase SRD5A reveals conserved steroid reduction mechanism - Yufei Han; Qian Zhuang; Bo Sun; Wenping Lv; Sheng Wang; Qingjie Xiao; Bin Pang; Youli Zhou; Fuxing Wang; Pengliang Chi; Qisheng Wang; Zhen Li; et al. (Nature Communications, 2021)
Steroid 5α-reductase 2 (SRD5A2), a testosterone metabolism enzyme, is implicated in human disease. Structural and biochemical analyses of PbSRD5A, a bacterial homolog, reveal SRD5A2 substrate binding pocket and provide framework for the design of new drugs targeting this enzyme.